Về các thành tạo địa chất Đệ tứ ở các đảo ven bờ Việt Nam - Ngọc, Nguyễn; Miên, Đào Thị (Vietnam Journal of Earth Sciences, 2001)
About quaternary geologic formations on the nearshore islands of Vietnam